RESERVOIR QUALITY REDUCTION CAUSED BY CLAY INDUCED DUCTILITY - Junita Trivianty Musu; Bambang Widarsono (Scientific Contributions Oil and Gas, 2010)
Ductile components including rock fragments, clay, and matrix material are often consideredas the most important factors that control quality of shaly sandstones, which are usually characterized by low porosity and permeability. In presence of ductile components, the degree of quality reduction is affected mainly by distribution, occurences, and amounts of the ductile components. Therefore, the presence of ductile components affects rock petrophysics, and consequently has effect on fluid movements in reservoir during production. This paper presents results of the study on plug samples taken from five wells from various fields in Cooper Basin (Tirrawarra Sand), South Australia. The samples were studied petrographically using x-ray diffraction, optical petrography, and scanning electrone microscope. The results were integrated with routine and special core analysis data. The overall results show that the distribution and the amount of ductile components have significantly reduced porosity, hence the quality of the reservoir. However, the effect is different for different types of porosity, and this certainly is valuable addition to our understanding over permeability behavior of shaly sandstones.